Promoting Public Transportation for Women: A Review of Factors Affecting the Mobility - Adilah Shamsul Harumain, Yong; Farhana Azmi, Nur; Mohamed Yusoff, Suhaini (International Journal of Engineering and Technology, 2019)
Globalization, urbanization, motorization, and socio-demographic transition have transformed travel pattern in particular in the growing mobility concerns on female public transportation user. Women mobility has been an interest in social and transportation studies due to the arising numbers of women working and travelling. The diversity social roles of women nowadays in family and workplace strongly define the travel-activity pattern of women. Hence, this paper aims to review factors affecting women mobility at the Light Railway Transit (LRT) stations. It is found that the factors affecting mobility of women users are significantly towards the facilities and the distance of the station to their destination. The preliminary survey also suggests the study of women behavior and their mobility are significant to promote the use of public transportation for women.Â